Potassium Nutrition Affects the Growth and Productivity of Onion Varieties - Ahmed, Mukhtar; Wahocho, Niaz Ahmed; Memon, Noor-un-Nisa; Jamro, Ghulam Murtaza; Kandhro, Muhammad Nawaz (Journal of Agriculture and Veterinary Science, 2024)
Potassium (K) plays a key role in onion growth and bulb formation. Therefore, analyzing how different onion varieties respond to varying potassium levels can help to optimize the potassium usage, enhance bulb quality and improve onion production resilience, ultimately leading to better economic returns. The present study explored the response of onion varieties to different potassium doses. Four K doses (0, 50, 75 and 100 kg ha-1) were tested using four onion varieties (Nasarpuri, Phulkara, Thano bulla khan and Ghotki). The significant nutritional effect was observed on all tested varieties. The increasing K supply (150 kg ha-1) exhibited better performance for growth and bulb related attributes. Significantly heavier plants with maximum height and neck diameter were recorded from higher K Supply over other K doses. The plants fertilized with adequate K nutrition retained the intensified physiological maturity. The higher K supply also exerted significant influence on bulb related traits. The bulb harvested from plots fertilized with increasing K nutrition had maximum weight and diameter with large scales. With regards to varieties, Nasapuri and Phulkara were found to be superior for all the traits over other varieties. Highest plant height, larger and heavier leaves were recorded in Nasapuri variety. The maximum bulb weight was also found in Nasapuri followed by Phulkara variety across the K treatments. The shorter plants with minimum bulb size and weight were harvested from Ghotki variety under all K conditions. The Ghotki variety also took more time to attain physiological maturity. It is concluded that onion varieties may be nourished with K @100 kg ha-1 for better growth and higher bulb production.
Keywords: Potassium rates; growth; productivity; onion; varieties